2014
DOI: 10.1371/journal.pone.0103392
|View full text |Cite
|
Sign up to set email alerts
|

Superior In Vitro Stimulation of Human CD8+ T-Cells by Whole Virus versus Split Virus Influenza Vaccines

Abstract: Pandemic and seasonal influenza viruses cause considerable morbidity and mortality in the general human population. Protection from severe disease may result from vaccines that activate antigen-presenting DC for effective stimulation of influenza-specific memory T cells. Special attention is paid to vaccine-induced CD8+ T-cell responses, because they are mainly directed against conserved internal influenza proteins thereby presumably mediating cross-protection against circulating seasonal as well as emerging p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 42 publications
2
8
0
Order By: Relevance
“…However, WIV induced higher upregulation of activation markers and increased production of cytokines as compared to SU vaccine. These results are consistent with previous studies by us and others ([ 8 , 21 ]. Moreover, the gene signature induced by WIV profoundly differed from the gene signature induced by SU.…”
Section: Discussionsupporting
confidence: 94%
“…However, WIV induced higher upregulation of activation markers and increased production of cytokines as compared to SU vaccine. These results are consistent with previous studies by us and others ([ 8 , 21 ]. Moreover, the gene signature induced by WIV profoundly differed from the gene signature induced by SU.…”
Section: Discussionsupporting
confidence: 94%
“…We have previously demonstrated that mice immunized intramuscularly with a whole inactivated H3N2 virus vaccine displayed high serum IgG2a antibody levels, indicative of a Th1 profile which with time and after the second immunization became a more mixed Th1/Th2 profile . Vaccines containing novel avian subtypes have generally been poorly immunogenic . Further work with an intramuscularly administered candidate pandemic avian whole inactivated H7N1 virus vaccine resulted in much lower levels of circulating antibodies .…”
Section: Discussionmentioning
confidence: 99%
“…There are three main formulations of inactivated vaccines: whole virus, split virus and subunit inactivated vaccines . The whole virus vaccine is highly immunogenic and is still used in some countries, but most vaccines produced after the 1970s have been split or subunit, due to the increased reactogenicity observed when using whole virus vaccines . Split and subunit vaccines are less reactogenic than whole virus vaccines, but remain immunogenic despite the removal of internal viral components .…”
Section: Introductionmentioning
confidence: 99%
“…Nucleoprotein (NP) and matrix 1 (M1) protein have been identified as major targets of immunodominant CD4 + and CD8 + T-cell responses [6,7], and the T-cell immunity induced upon vaccination can explicate the superior protection afforded by split vaccines than protection by subunit vaccines which lack NP and M1 [8]. Whole-virion vaccines, in turn, are considered more immunogenic and cross-reactive than split vaccines due to the better structure of vaccine antigens that can be much more effectively presented by dendritic cells and macrophages to T cells through MHC-class I and II restricted manner [9].…”
Section: Reassortant Viruses For Influenza Vaccines: Is It Time To Rementioning
confidence: 99%